The association between diet and mood: A systematic review of current literature. (January 2019) - Arab, Arman; Mehrabani, Sanaz; Moradi, Sajjad; Amani, Reza
Highlight: According to our best knowledge, no systematic review study has previously assessed the effects of different type of diets on mood. Since diet contains the interactions between its components, it can, therefore, play more important role on mood and mental health rather than single nutrients and food items. Accordingly, we decided to assess the relationship between different types of diet with mood states thorough this systematic review. Abstract: A number of studies have examined the association between diet and mood state, but the findings have been inconclusive. Herein, we conducted a systematic review to assess the association between different diet and mood state. PubMed, Cochrane's library, Science direct, Scopus, Google scholar and ISI web of science databases were searched for all available literature until December 2017 for studies assessing the association between diet and mood state. The Newcastle-Ottawa Scale and Jadad scale for reporting randomized clinical trials were used to assess study quality. A total of 18 studies out of 2857 met our inclusion criteria and included in our systematic review. Although there are not consistent findings between studies, it seems that DASH, vegetable-based, glycemic load-based, ketogenic and Paleo diets could improve mood more than the others. Further studies are needed to assess such relationship in a longer period to draw a firm link between diet and mood.